Sources and Prospects for Revenue Mobilization in Baglung Municipality - Silwal, Sudarshan (Economic Journal of Development Issues, 2010)
The main aim of this paper is to highlight the sources of revenue collection and explore the revenue potentialities of Baglung Municipality. This paper was prepared by reviewing the contemporary literature related to these issues and analyzing the information/data derived from the field survey and the feedbacks received from four informal meetings with former mayors, deputy mayors, ward chairpersons and executive officers of the municipality. This study describes a brief sketch of municipal revenue and its trends, municipal resource mobilization and its legal provisions, major issues in revenue mobilization and management and revenue generation potentialities. It is found that the Local Development Fee is the largest revenue source which comprises 44.51% of own sources of revenue and more than 27.05% of total revenue of the Baglung Municipality. The share of local development fee in own sources of revenue and total revenue in case of Pokhara Sub-metropolitan city and Butwal Municipality are higher than that of Baglung Municipality. Likewise, it is also found that the percentage share of internal sources in the total municipal revenue has been declining and municipal expenditure covered by this source has been fluctuating between 67.75 % to 25.77%. Baglung Municipality has the possibility of raising revenue from new sources. Such sources may include tourist entry fee, hat market fee, entertainment tax, personal income tax, tax on animal, business tax, advertisement tax, integrated property tax, vacant land tax, local government reform fee, lodger’s tax, cigarette tax, traffic safety fee and tax on feast etc. Key words: Municipality; Local governance; Resource mobilization; Prospects; Revenue; Expenditure. Economic Journal of Development Issues Vol. 9 and 10 (2008 & 2009) Combined Issue Page: 137-154